2014 16th European Conference on Power Electronics and Applications 2014
DOI: 10.1109/epe.2014.6910986
|View full text |Cite
|
Sign up to set email alerts
|

Power converters design and analysis for high power piezoelectric ultrasonic transducers

Abstract: High power piezoelectric ultrasonic transducers have been widely exploited in a variety of applications. The critical behaviour of a piezoelectric device is encapsulated in its resonant frequencies because of its maximum transmission performance at these frequencies. Therefore power electronic converters should be tuned at those resonant frequencies to transfer electrical power to mechanical power efficiently. However, structural and environmental changes cause variations in the device resonant frequencies whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Figure 4 shows the variation of f o of the system with increasing l c from 0 mm to 22 mm. The drop in the f o from the f i correlates with research work in which resonance frequency is found to be the lowest frequency within the impedance curve [36]. The output power of the system gradually increases with l c due to its approach near resonance frequency, which allows efficient transmission of the ultrasonic power to the material.…”
Section: Resultssupporting
confidence: 56%
“…Figure 4 shows the variation of f o of the system with increasing l c from 0 mm to 22 mm. The drop in the f o from the f i correlates with research work in which resonance frequency is found to be the lowest frequency within the impedance curve [36]. The output power of the system gradually increases with l c due to its approach near resonance frequency, which allows efficient transmission of the ultrasonic power to the material.…”
Section: Resultssupporting
confidence: 56%
“…However, the resonant frequency of the transducer can be easily changed during its operation due to environmental and structural changes. The effect of the transducer resonant frequency changes on its energy conversion performance was thoroughly studied in (Ghasemi, 2012;Ghasemi et al, 2012;Davari et al, 2014) and it was shown that the transducer performance is degraded with the change of its resonant frequency. Therefore, detecting the resonant frequency of the transducer and adjusting the operating frequency of the system during the real-time operation is necessary for efficient energy conversion.…”
Section: Treatment Methodsmentioning
confidence: 99%
“…Therefore, detecting the resonant frequency of the transducer and adjusting the operating frequency of the system during the real-time operation is necessary for efficient energy conversion. To address this issue, an online algorithm was developed in (Davari et al, 2014) to measure the main resonant frequency of the transducer during the real-time operation. Any change in the main resonant frequency of the transducer can be detected using this algorithm.…”
Section: Treatment Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resonance frequency is found by plotting the impedance frequency response (Fig. 4.6) [100]. The resonance occurs when the impedance of the piezoelectric element is at its lowest.…”
Section: Mathematical Formulationmentioning
confidence: 99%